Exergy analysis of a multi mixture working fluid absorption refrigeration cycle. (November 2019) - Mohtaram, Soheil; Omidi, Mohammad; Lin, Ji; Sun, Hongguang; Chen, Wen
Abstract: This research paper analyzes the exergy of an absorption refrigeration cycle with a multi mixture working fluid selected as water and lithium-bromide. It relies on the fundamental thermodynamic principles, being chiefly the first and second laws. The exergy destructions have been obtained from different parts of the cycle; after which several components are analyzed in terms of their thermodynamics efficiency. Additionally, exergy efficiency and coefficients of performance (COP) are thoroughly investigated. It can be observed from the results of the simulations; the greatest rate of the destruction of exergy exists in the absorber and is 35.87% of the destruction. Such irreversibility is primarily caused by the heat transfer of high-temperature variation. Future improvements may include increasing the rate of heat exchange, which thereby reduces the temperature variation.